2018
DOI: 10.1002/pbc.26938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline clinical and laboratory features on the risk of thrombosis in children with acute lymphoblastic leukemia: A prospective evaluation

Abstract: Older age, non-O blood group, and presence of circulating blasts, but not PDs, predicted the risk of sTE during ALL therapy. We recommend evaluation of these novel risk factors in the development of ALL-associated TE. If confirmed, these easily accessible variables at diagnosis can help develop a risk-prediction model for ALL-associated TE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 54 publications
2
27
1
Order By: Relevance
“…This study demonstrated that VTE occurred in 7.6% of children during ALL treatment. Multivariable analyses using a case‐control design showed that age ≥7 years was a main risk factor for VTE, thus confirming other studies 24,25 . Accordingly, it is recommended to include age in preventive strategies for VTE during ALL treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that VTE occurred in 7.6% of children during ALL treatment. Multivariable analyses using a case‐control design showed that age ≥7 years was a main risk factor for VTE, thus confirming other studies 24,25 . Accordingly, it is recommended to include age in preventive strategies for VTE during ALL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…showed that age ≥7 years was a main risk factor for VTE, thus confirming other studies. 24,25 Accordingly, it is recommended to include age in preventive strategies for VTE during ALL treatment. An analysis of the developmental hemostatic system showed a relative protective effect against VTE in young infants, compared with adults, with decreased levels of several critical procoagulant factors and increased levels of certain natural anticoagulants.…”
Section: Treatment and Outcome Of Vtementioning
confidence: 99%
“…8 In children, older age (>7 or 10 years) is one of the main risk factors of symptomatic TE. 1,4,8 Chemotherapeutic agents including Lasparaginase and corticosteroids further enhance the hypercoagulable state. 2,3 In our 9-year-old patient, a huge thrombus was found in the RV, not in common sites of TE such as the upper or lower extremities or central venous sinus.…”
Section: A Huge Right Ventricular Thrombosis and Pulmonary Thromboembmentioning
confidence: 99%
“…One recent study reported that T‐cell subtype of ALL is significantly associated with the development of venous TE 8 . In children, older age (>7 or 10 years) is one of the main risk factors of symptomatic TE 1,4,8 . Chemotherapeutic agents including l ‐asparaginase and corticosteroids further enhance the hypercoagulable state 2,3 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation